In-Vivo Imaging of Ocular Microvasculature Using Swept-Source Optical Coherence Tomography Angiography in Seven Types of Lab Animals - Wu, Xuan; Chua, Jacqueline; Ho, Candice; Yao, Xinwen; Muralidharan, Arumugam R.; Najjar, Raymond P.; Tan, Gavin; Tamm, Ernst R.; Schmetterer, Leopold; Barathi, Veluchamy A.; Tan, Bingyao (Frontiers in Photonics, 2022)
The purpose of this study is to characterize the retinal and choroidal vascular networks in some of the most common animal species using swept-source optical coherence tomography angiography (SS-OCTA). Retinal angiographic images were acquired from healthy, anesthetized animals of seven species (mouse, rat, pig, rabbit, guinea pig, chicken, and non-human primate). We generated the enface angiograms to visualize the different retinal vascular plexuses and the choroidal vascular plexus. Quantitative OCTA metrics, including perfusion density, vessel density, and fractal dimension, were compared amongst the different species. There was a noticeable difference in the OCTA enface maps of the distinct vascular layers amongst the various species. Specifically, the non-human primate retina has the highest level of perfusion density and vessel density, whereas the rabbit retina exhibited the lowest level of vessel density. The mouse and the rat retina shared similar vascular patterns, and there was no difference in the OCTA metrics. Using one specific SS-OCTA system for all experiments eliminated multiple instrument-dependent factors, but the lateral resolution was still affected by eye size. Effects of varying lateral resolution on vascular metrics were investigated via a simulation. Overall, we achieved a large field of view of the distinct retinal and choroidal vascular plexuses and quantified the vascular metrics in multiple species, which offers opportunities to study the retinal and choroidal vascular abnormalities and their roles in ocular diseases resembling in-vivo histology.